2022
DOI: 10.1002/ijc.34401
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of brain gliomas using plasma cell‐free DNA 5‐hydroxymethylcytosine sequencing

Abstract: Liquid biopsy techniques based on deep sequencing of plasma cell-free DNA (cfDNA) could detect the low-frequency somatic mutations and provide an accurate diagnosis for many cancers. However, for brain gliomas, reliable performance of these techniques currently requires obtaining cfDNA from patients' cerebral spinal fluid, which is cumbersome and risky. Here we report a liquid biopsy method based on sequencing of plasma cfDNA fragments carrying 5-hydroxymethylcytosine (5hmC) using selective chemical labeling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We included 5hmC sequencing data from 33 LUAD [18] , 74 PDAC [20] , 132 HCC [21] , 72 GBM [22] and 85 control [20] samples. All samples belonged to one study, and get published in four publications.…”
Section: Resultsmentioning
confidence: 99%
“…We included 5hmC sequencing data from 33 LUAD [18] , 74 PDAC [20] , 132 HCC [21] , 72 GBM [22] and 85 control [20] samples. All samples belonged to one study, and get published in four publications.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al built a data set containing 180 glioma patients and 229 nonglioma controls by collecting venous plasma. A penalized logistic model constructed with training set differentially hydroxymethylated genes (DhmGs) could help glioma diagnosis in both test set (AUC = 0.962) and an independent data set (AUC = 0.930) consisting of 111 gliomas and 111 controls [82].…”
Section: Multiomics Advances In Cancer Subtypingmentioning
confidence: 99%
“…Several studies have reported attempts to identify and grade gliomas based on the analysis of nonspecific molecular and cellular components in a patient's blood such as glial fibrillary acidic protein, other proteins, and neutrophil/lymphocyte ratios [16][17][18][19]. Similarly, the identification of IDH mutations based on circulating DNA [20], and the usefulness of hydroxy methylome analysis of circulating DNA in plasma [21] have also been reported. Each of these methods, which focus on specific components, require different sample-processing methods and reagents, and costs for each component.…”
Section: Introductionmentioning
confidence: 99%